A study of young peoples' attitudes to opportunistic Chlamydia testing in UK general practice - Jones Melvyn; Heritage Joanne (Reproductive Health, 2008)
Abstract Objective The objective of this study was to assess young people's perceptions of being offered a chlamydia screening test in United Kingdom (UK) general practice. Methods This is qualitative study that uses focus groups and individual interviews with young adults (age 16 – 18) to assess their views. Results These young adults were a difficult group to gain access to. Two focus groups, one in a school, the other in a general practice (family practice), and 2 individual interviews were undertaken (total sample 18). Respondents were unfamiliar with Chlamydia, but broadly aware of sexually transmitted infections. General practice (family practice) was perceived as an acceptable place to deliver opportunistic screening, but participants felt that tests should not be initiated by GP receptionists. Novel delivery routes such as schools and "Pub"/Bar dispensing machines were discussed. Issues around stigma and confidentiality were also raised. Conclusion Opportunistic Chlamydia screening in UK general practice (family practic seems acceptable to young adults. While this is a difficult group to gain access to for research, attempts need to made to ensure acceptability to users of this programme.